Self-Concept as a Determinant of Ethical Behavior in Organizational Professional Practice - Intan Ratna Sari Yanti; Syaiful Ali (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The development of modern organizations requires individuals not only to possess professional competence but also to demonstrate ethical behavior in carrying out their professional responsibilities. However, many organizations still face challenges related to inconsistent ethical behavior among professionals, indicating a gap between ethical standards and actual practice; therefore, this study aims to examine the role of self-concept as a determinant of ethical behavior in professional settings. Ethical behavior in organizations is influenced not only by external regulations such as professional codes of conduct but also by internal psychological factors within individuals. One of the most important internal factors is self-concept, which reflects how individuals perceive and understand themselves in relation to their roles and responsibilities in the workplace. This research employs a qualitative approach, using in-depth interviews and documentation to obtain comprehensive insights into individual perceptions and experiences of ethical behavior in professional settings. Purposive sampling is used, and the data are analyzed through thematic analysis. The results indicate that individuals with a clear and positive self-concept tend to demonstrate stronger moral awareness, greater responsibility, and more consistent ethical decision-making, with key themes including self-awareness, moral responsibility, ethical consistency, and organizational support. Furthermore, organizational culture and ethical leadership reinforce the development of self-concept that supports ethical behavior. This study provides empirical insight into the psychological basis of ethical behavior and offers practical implications for strengthening organizational integrity.